IDE-OTALEX C. The First Crossborder SDI between Portugal and Spain: Background and Development - Batista, Teresa (2014)
IDE-OTALEX is the first crossborder spatial data infrastructure between contiguous Portuguese (Alentejo and Centro) and Spanish (Extremadura) regions. It was implemented to share official geographic information from Alentejo and Extremadura, and now Centro region, with everyone. This is the most effective way to have a distributed and flexible system to be used as a territorial observatory for sustainable development and environment protection in these rural and low populated regions. It also contributes to territorial cohesion, one of the tree main pillars of European Cohesion Policy. It’s characterized for being a distributed, decentralized, modular and collaborative system, based on standards OGC (Open Geospatial Consortium), W3C (World Wide Web Consortium), ISO (International Organization for Standardization) and open source technology, developed to guarantee interoperability between the different GIS (Geographic Information System) provided by each project partner. The geoportal is multilingual (Portuguese, Spanish and English) and integrates a Map viewer, Metadata Catalogue and Gazetteer. It consists in central and local nodes which communicate through WMS (Web Map Services), CSW (Catalogue Service Web) and WFS (Web Feature Services). It is now implementing SOS (Sensor Observation Services) and WPS (Web Map Processing). The geographic information available results of an extensive work of data harmonisation adapted to INSPIRE Directive (D 2007/2/EC, the European Parliament and Council, March 14, 2007). It integrates basic cartography, socio-economic, territorial and environmental indicators.